Glut: Affective Labor and the Burden of Abundance in Secondhand Economies. (21st June 2022) - Berry, Brieanne
Abstract: This paper explores the interlinkages between the abundance of stuff moving through community‐based reuse organizations and the labor needed to manage this material. The glut of donations is due to the sheer volume of materials moving through a wasteful linear economic system, as well as the practice of donation dumping, where unusable used goods move through reuse economies, washing their previous owners free of guilt while entangling laborers in messy relationships with objects. I draw on theories of gendered, social reproductive labor to explore how the work of localized reuse, disproportionately borne by unpaid women, reproduces communities. Following calls for work that explores the social dimensions of circular economies, this research uses a qualitative approach that draws on two main methods: participant observation in reuse establishments and in‐depth interviews with reuse participants. This qualitative data provides a picture of reuse activities at a local scale and helps us understand the complex relationships formed and perpetuated through reuse. I find that the labor of volunteers is often unseen and undervalued and suggest that policies designed to address material surplus do so with these laborers in mind.